"Backstage" Responses to the Sydney Siege: A Case-study of the Sermons Delivered in the Mosques of Sydney in the Aftermath of the Incident. Issue 2 (2nd April 2020) - Underabi, Husnia
Abstract: Sydney's December 2014 Lindt Café siege resulted in the death of two hostages and of the perpetrator. In February 2015, Prime Minister Tony Abbott argued Muslim leaders were not doing enough to tackle violent extremism. To examine this point, this paper analyses 13 mosque sermons delivered across 10 mosques (and 1 community hall) in Sydney immediately after the 2014 Lindt Café siege. It shows that what was said in the sermons was consistent with what was said by community leaders publicly-that the incident was condemned, considered to be un-Islamic, the perpetrator was mentally ill, and his victims were innocent. Audiences were told that the consequence of killing innocent people is eternal damnation. Some sermons acknowledged that non-Muslims may be confused and have a negative view of Islam and members of the congregations were asked to reach out to non-Muslims and demonstrate that Islam is a religion of peace.